Implementing Telemedicine Visits in an Underserved Ophthalmology Clinic in the COVID-19 Era - Mona Adeli; William R. Bloom (SAGE Publishing, 2021)
Introduction: Many of the potential barriers to providing telehealth services already disproportionately impact vulnerable populations. The purpose of this study was to assess the incorporation of synchronous ophthalmology telemedicine visits in a tertiary university-based ophthalmology clinic for low-income and uninsured patients in the COVID-19 era. Methods: The records of 18 patients who were due for an in-person visit in the medically underserved patient clinic at our institute were reviewed. Patients considered high risk of ocular morbidity progression were approved to proceed with an in-person visit. Patients with non-urgent visit indications were attempted to be contacted by telephone to be offered a telemedicine telephone visit as an alternative to a postponed in-person office visit. Results: Clinical triage by an attending ophthalmologist determined that 17 patients (94.4%, n = 18) had visit indications appropriate for evaluation by telemedicine. Six patients (35.3%, n = 17) were successfully contacted and offered a telemedicine visit as an alternative to a postponed in-person office visit. All 6 patients accepted, scheduled, and completed a telemedicine visit. Eleven patients (64.7%, n = 17) were not able to be successfully contacted to offer and schedule either a telemedicine visit or a postponed in-person office visit. Patients who were not able to be successfully contacted were on average younger in age and more likely to be female, Hispanic/Latino, from Latin America, with a preferred language of Spanish. Conclusions: Synchronous ophthalmology telemedicine visits can be successfully incorporated in a tertiary university-based setting for low-income and uninsured patients. The primary barrier to providing telemedicine visits in this population was the ability to successfully contact patients to offer and schedule these visits.